The nexus between corruption and opportunistic crimes during Covid-19 in South Africa - Mmakwena, Modipa; Moses, Motseki (Technium Social Sciences Journal, 2022)
Covid 19 in South Africa created opportunity for criminals to enrich themselves at the expense of the poor. Public and private sector officials benefited due to irregular tenders and overpricing of personal protective equipments in South Africa as reported on media platforms. This article explores opportunistic crimes associated with Covid 19 and their impact on the fight against the pandemic. This qualitative article adopted a non-empirical research design: Systematic review, indirect observation schedules to identify and describe available research literature ‘using systematic and explicit accountable methods and pre-specified formalised tools for searching and integrating literature. The data was collected from January-July 2021. The collected data was analysed through inductive textual content analysis. Findings revealed that public officials benefited from irregular PPE tenders as well as friends and families of politicians. The findings further indicate that billions of Rands were looted from funds which were meant to fight Covid 19 in South Africa. Lastly the findings show that law enforcement agencies are not effective in dealing with cases of Covid 19 crimes. Based on the findings, the following recommendations were developed: Law enforcement agencies should be equipped with resources to deal with Covid 19 crimes and ensure successful prosecution of those crimes, Competition Commission should investigate the companies which benefited from irregular tenders and overpricing of PPE’s so that they could be held accountable. Public participation should be strengthened to combat crime.